The SAGE handbook of research in international education - Hayden, Mary; Levy, Jack; Thompson, J. J. (John Jeffrey), 1938- (Los Angeles : SAGE, 2016)
This work analyses the origins, contributions, and interpretations of international education. The authors identify approaches to research that will progress our knowledge and understanding of the field, and extend and even redraw it, on the basis of the research evidence presented.
Previous edition: 2007.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 8, 2016).
Keywords: International education -- Research